ASSOCIATION OF RAISED WHITE BLOOD CELL AND NEUTROPHIL COUNTS WITH SPONTANEOUS STONE PASSAGE IN PATIENTS PRESENTING WITH ACUTE RENAL COLIC - Muhammad Seerwan; Muhammad Muzammil Tahir; Rana Ata Ur Rehman (Journal of University Medical & Dental College, 2016)
ABSTRACTINTRODUCTION: Ureteric stones are a common urologic problem and presents usually with a severe colicky pain. There are a wide range of options available for the treatment of ureteric calculi ranging from conservative management to minimal invasive options such as ESWL and ureterorenoscopy to more invasive modalities e.g laproscopic ureterolithotomy and open ureterolithotomy. Selection of patient who are best candidates for conservative management is a difﬁcult decision. There are some known factors such as stone size and location, e.g small stone size and distal ureteric calculi have more chances of the spontaneous. But there are still some factors who are to be investigated. This study is carried out to investigate the association of raised WBCs and neutrophil counts with the spontaneous passage of ureteric calculi.MATERIALS AND METHODS: 190 patients (95 in each group) with ureteric calculi fulﬁlling the inclusion criteria were registered through emergency and OPD of sheikh zayed hospital Lahore, Pakistan. They were allotted two groups. The patients with raised WBCs and neutropil counts at presentation were allocated Group A and patients without raised WBCs and neutropil counts were put in Group B. All the patients were managed on NSAIDs in case of pain and followed for 4 weeks for spontaneous passage of ureteric stones. For comparison, chi-square test was applied. P <0.05 was taken as signiﬁcant. RESULTS: A total of 190 cases of ureteric stones divided equally into two groups have average stone size of 7.45±1.16 mm (range 5.0-10.0 mm) Spontaneous passage of stone was noted in 147(77.4%) cases while it was not passed in 43(22.6%) cases. Spontaneous passage of stone was noted in 85(57.8%) cases in group A, who have raised WBCs and neutrophil counts, while in 62(42.2%) cases in group B, who are without raised WBCs and neutrophil counts and this difference was statistically signiﬁcant (p-value=0.000)CONCLUSION: We conclude that the raised WBCs and neutrophil counts can signiﬁcantly contribute to the prediction of spontaneous passage of ureteric stones in patients presenting with acute ureteric colic. To maximize their predictive ability they should be combined with other factors such as the stone size and the location.